TREATMENT OF TRAUMATIZED MAXILLARY PERMANENT CENTRAL INCISORS. A CASE REPORT - Radosveta S. Andreeva (Peytchinski Publishing, 2020)
Traumatic injury to the upper anterior teeth is common in young children, especialy when it is combined whit orthodontic problem - overjet. This paper reports the presence of traumatized maxillary permanent central incisors which are successfully restored whit wax-up technique. Case report: The case describe the treatment of traumatized maxillary permanent central incisors whit wax-up technique. A 9-year-old girl came to the dental clinic with an injury of the two maxillary central incisors with oblique partial crown fracture without pulp exposure. Traumatized anterior teeth require quick functional and esthetic repair, and wax-up technique is commonly used for their restoration. The wax-up technique seems to be a promising restorative option. This is a rational restorative alternative and less invasive prosthodontic treatment. The patient and the parents are satisfied whit the result which confirmed the success of the rehabilitation.